Environmental sustainability regulatory and policy practices and actions of telecoms regulatory authorities - Mester, Máté (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
Creating climate-neutral electronic communications is a shared responsibility for the industry and urgent action is needed in the face of warming trends due to global climate change. Despite this, environmental sustainability has just started to receive attention in the regulation of the electronic communications sector. The national telecoms regulatory authorities overseeing the sector in the different countries are key in driving related policy and regulation. However, as to date, hardly any paper has dealt with their respective practices in a comparative manner. Therefore, the aim of this paper is to fill this gap, to review the relevant environmental sustainability regulatory and policy practices and actions of telecoms regulatory authorities, in order to provide a comprehensive and high-level comparison of sustainability initiatives in the electronic communications sector. It is hoped that this will serve as a starting point for launching a discourse in the industry and for properly positioning the green transition in electronic communications regulation.